Information Science Academic Members of Iranian Public Universities Sharing Information Resources in ResearchGate Social Scientific Network: It's Relation on their Scientific Output in Scopus Database and Google Scholar Search Engine - Abbas Doulani; Zahra Shabani; Roya Baradar (Tehran University of Medical Sciences, 2020)
Background and Aim: The purpose of the present study was to investigate the scientific outputs of the faculty members of the information science and science departments of Iranian state universities in the Science Research Network and its impact on their scientific outputs in databases and search engines. Materials and Methods: This study was applied in terms of purpose, survey methodology and Altmetrics approach. The statistical population of the study consisted of 118 faculty members in the field of information science and social sciences active in Social- Scientific Network from 29 Governmental universities in the country. Pearson correlation coefficient, independent t-test, Kruskal-Wallis were used for data analysis. Results: The findings showed that the authors of Isfahan, Tehran University of Medical Siences and Shahid Chamran of Ahvaz Universities are the most active members of the faculty in ResearchGate in terms of Altmetrics characteristics. In terms of RG score, faculty members with associatechr('39')s degree perform better than the others. There is also a positive correlation between the Altmetrics indicators of ResearchGate network and the scientometric indicators of Scopus citation database and Google Scholar. Conclusion: Since there was a positive correlation between Altmetrics indexes in ResearchGate with Scinientometrics indexes in Google Scholar and Scopus, so this leads to the visibility of their scientific work and their improvement of citation indexes in databases.